PENGARUH INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) TERHADAP KUALITAS LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL PEMODERASI - Risa Rukmana (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study aimed to examine the effect of the application of International Financial Reporting Standards (IFRS) and the quality of earnings to see how companies audited by the BIG 4 and KAP KAP Foreign Affiliates as moderating variables. The population in this research is manufacturing companies listed in Indonesia Stock Exchange in 2009-2014. Hypothesis testing is done by multiple regression test. The results showed no significant effect of adoption of IFRS by the quality of earnings. That is, after the adoption of IFRS did not make the quality of earnings reported by companies is increasing. Quality audits as an independent profession is also not proven to provide better impact after implementation of IFRS with earnings quality.